1988
DOI: 10.1098/rspb.1988.0056
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical design of nacre

Abstract: Mother-of-pearl (nacre) is a platelet-reinforced composite, highly filled with calcium carbonate (aragonite). The Young modulus, determined from beams of a span-to-depth ratio of no less than 15 (a necessary precaution), is of the order of 70 GPa (dry) and 60 GPa (wet), much higher than previously recorded values. These values can be derived from ‘shear-lag’ models developed for platey composites, suggesting that nacre is a near-ideal material. The tensile strength of nacre is of the order of 170 MPa (dry) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
307
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,036 publications
(324 citation statements)
references
References 25 publications
6
307
1
1
Order By: Relevance
“…Its stiffness is on the same order as mineral, but its strength is two to three times higher than that of mineral. Specifically, the fracture toughness of a nacre structure is 3000 times higher than that of a monolithic mineral [16][17][18][19]. Thus far, the mechanical properties of even man-made ceramic cannot reach such a high level [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Its stiffness is on the same order as mineral, but its strength is two to three times higher than that of mineral. Specifically, the fracture toughness of a nacre structure is 3000 times higher than that of a monolithic mineral [16][17][18][19]. Thus far, the mechanical properties of even man-made ceramic cannot reach such a high level [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Nature, on the other hand, can assemble to perfection complex composite materials for a variety of functions. For example, the abalone shell is made out of calcium carbonate and organic matrices, or bone that is composed of calcium phosphate and collagen fibres, both of which display excellent mechanical properties 8,9 . In most cases, these materials are constructed very slowly, and are perhaps not viable for technological applications.…”
mentioning
confidence: 99%
“…These structural biological materials are sophisticated hierarchical composites based on brittle minerals and ductile polymers, which can exhibit mechanical properties that are far beyond those that can be achieved using the same synthetic compounds (Meyers et al 2008a). In particular, the principles of biologically controlled self-assembly in seashells have generated much recent interest (Jackson et al 1988;Kamat et al 2000;Evans et al 2001;Wang et al 2001;Rubner 2003;Mayer 2005); indeed, it has been suggested that their sophisticated structures can offer guidelines for the development of new generations of structural materials (Ortiz & Boyce 2008;Aizenberg & Fratzl 2009). …”
Section: Introductionmentioning
confidence: 99%